The severity of depression is associated with pelvic inflammatory diseases: A cross-sectional study of the United States National Health and Nutrition Examinations from 2013 to 2018 - Huang, TianJiao; Cao, RenShuang; Liu, PengFei; Liu, JinXing; Yu, Xiao (Frontiers in Medicine, 2022)
Purpose : To investigate the relationship between depression severity and risk factors for pelvic inflammatory diseases (PID) to generate new knowledge about treatment options. Patients and methods : Multivariate regression was used to evaluate the association be-tween pelvic inflammatory disease and the severity of depression. Females who participated in the United States National Health and Nutrition Examination Survey (NHANES) from 2013 to 2018 were included. Results : The risk of pelvic inflammatory disease was positively correlated with the in-crease of depression index (odds ratio, OR 1.10, 95% confidence interval, CI 1.08–1.12), especially in people with severe depression (odds ratio, OR 6.34, 95% confidence interval, CI 3.72–10.79). Conclusions : This study showed that depressive state is significantly related to PID events, and severe depressive state brings a greater risk of PID in The United States.